1998
DOI: 10.1074/jbc.273.11.6495
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Metabotropic Glutamate Receptor and Protein Kinase C Reduce the Extent of Inactivation of the K+Channel Kv1.1/Kvβ1.1 via Dephosphorylation of Kv1.1

Abstract: Various brain K؉ channels, which may normally exist as complexes of ␣ (pore-forming) and ␤ (auxiliary) subunits, were subjected to regulation by metabotropic glutamate receptors. Kv1.1/Kv␤1.1 is a voltage-dependent K ؉ channel composed of ␣ and ␤ proteins that are widely expressed in the brain. Expression of this channel in Xenopus oocytes resulted in a current that had fast inactivating and noninactivating components. Previously we showed that basal and protein kinase A-induced phosphorylation of the ␣ subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…These data may suggest that complete PKC block is required to shift the activation curve, whereas only a partial block is needed to inhibit inactivation. Alternatively, different PKC isoforms could be involved that show differential inhibitor sensitivity, as has been previously described by other investigators in other systems (23,26,27). Inhibitor peptides that block Ca 2ϩ -dependent PKC isoforms did not alter Kv1.5/Kv␤1.3 interaction (data not shown).…”
mentioning
confidence: 65%
“…These data may suggest that complete PKC block is required to shift the activation curve, whereas only a partial block is needed to inhibit inactivation. Alternatively, different PKC isoforms could be involved that show differential inhibitor sensitivity, as has been previously described by other investigators in other systems (23,26,27). Inhibitor peptides that block Ca 2ϩ -dependent PKC isoforms did not alter Kv1.5/Kv␤1.3 interaction (data not shown).…”
mentioning
confidence: 65%
“…The final effector of gintonin-mediated LPAR activation is likely to be the blockade of voltagedependent potassium channels. Previously, it was reported that the PLC-PKC pathway inhibits the action of voltage-dependent potassium channels (Boland and Jackson 1999;Levy et al 1998). In addition, a recent study showed that gintonin application in artificial expressing systems inhibits Kv 1.2 channels .…”
Section: Discussionmentioning
confidence: 98%
“…The Group I family includes mGlu1 and mGlu5 receptors; activation of these receptors stimulates phospholipase C, resulting in phosphoinositide hydrolysis and elevation of intracellular Ca 2 þ levels. Group I mGlu receptors have also been shown to modulate ion channels such as K þ channels (Ikeda et al, 1995;Levy et al, 1998), Ca 2 þ channels (Takahashi et al, 1996;McCool et al, 1998), and nonselective cation channels (Zhou and Hablitz, 1997).…”
Section: Introductionmentioning
confidence: 99%